2005
DOI: 10.1111/j.1365-2036.2005.02629.x
|View full text |Cite
|
Sign up to set email alerts
|

Carriage of CARD15 variants and smoking as risk factors for resective surgery in patients with Crohn's ileal disease

Abstract: Summary Background:  It is controversial whether CARD15 variants are truly associated with a more severe form of Crohn's disease. The relative role of CARD15 genotype and smoking in Crohn's disease progression is also debated. Aim:  To investigate the association between CARD15 variants and history of resective surgery in patients with Crohn's ileal disease, taking into account smoking as a possible confounding factor. Methods:  We originally assessed CARD15 genotype in 239 north Italian Crohn's disease patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Reports regarding an association between CARD15 mutations and a positive family history for IBD are, however, not consistent. While some studies reported a significant association [20,40,42,55,77], most did not [15,25,33,38,41,43,53,[78][79][80][81][82]. In this study, we also found no association between CARD15 carriage and a positive familial history, although the number of patients without a familial history was relatively low compared with the group of familial patients.…”
Section: Discussioncontrasting
confidence: 74%
“…Reports regarding an association between CARD15 mutations and a positive family history for IBD are, however, not consistent. While some studies reported a significant association [20,40,42,55,77], most did not [15,25,33,38,41,43,53,[78][79][80][81][82]. In this study, we also found no association between CARD15 carriage and a positive familial history, although the number of patients without a familial history was relatively low compared with the group of familial patients.…”
Section: Discussioncontrasting
confidence: 74%
“…3,9,[12][13][14] Given that cigarette smoking can accelerate the risk of surgery, 23 the rates of current and/or past smokers were compared with nonsmokers in patients positive or negative for ASCA or Gly908Arg. In view of the fact that young age at diagnosis of CD is associated with more severe disease, 24,25 the age at disease diagnosis in patients with and without ASCA or NOD2/ CARD15 mutations were compared.…”
Section: Discussionmentioning
confidence: 99%
“…1) (de Diego et al, 2006, Helbig et al, 2012, Mendoza et al, 2003, Mardini et al, 2005). An additional 14 studies were included after obtaining SNP-specific data from study authors (Ananthakrishnan et al, 2014, Cleynen et al, 2013, Doecke et al, 2015, Giachino et al, 2004, Henckaerts et al, 2009, Karban et al, 2011, Laghi et al, 2005, Lakatos et al, 2005, Latiano, 2008, Nagy et al, 2005, Protic et al, 2008, Renda et al, 2008, Sabate et al, 2008, Walker et al, 2004). One study providing SNP-specific data was excluded from the analysis due to small cell sizes (Lauriola et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Our systematic review demonstrated that the majority of NOD2 -smoking studies were underpowered to detect an interaction; for example, 10 identified studies included fewer than 300 participants (de Diego et al, 2006, Giachino et al, 2004, Laghi et al, 2005, Mardini et al, 2005, Mendoza et al, 2003, Protic et al, 2008, Renda et al, 2008, Sabate et al, 2008, Walker et al, 2004, Nagy et al, 2005). Because of these small samples, the three most common NOD2 variants (1007fs, G908R, and R702W) were often combined.…”
Section: Discussionmentioning
confidence: 99%